Pengaruh Kadar Aspal dan Kepadatan pada Nilai Kekesatan (Skid Resistance) Permukaan Perkerasan Beton Aspal Lapis Aus - Mashuri, M.; Syahbani, D.; Labaso, E.R.; Rahman, R. (Tadulako University, 2024)
Asphalt concrete wearing course is located on the topmost surface layer so that this layer is indirect contact with vehicle wheels and other environmental factors, such as sunlight, rainwater. This condition makes asphalt concrete wearing course pavement susceptible to wear on the surface layer. This condition causes wear on the surface of the asphalt concrete wearing course pavement, so that the surface becomes slippery because the skid resistance decreases, especially in wet conditions. The large asphalt content and density of the mixture can affect the skid resistance of the asphalt concrete wearing course surface. The purpose of this study was to determine the effect of bitumen content and density on the skid resistance value of the asphalt concrete wearing course surface. This research was conducted at the Transportation and Highway Laboratory, Tadulako University. This study used five variations of asphalt content, namely 5.0%, 5.5%, 6.0%, 6.5% and 7.0% by weight of the mixture. Measurement of the skid resistance value of the asphalt concrete wearing course pavement surface using the British Pendulum Tester (BPT). The measurement procedure is based on SNI 4427: 2008. One-way ANOVA Method with a significance level of 95% is used to determine the effect of asphalt content and density on the surface skid resistance value of asphalt concrete wearing course pavement. The results of this study found that asphalt content and pavement density had affected the skid resistance value of the asphalt concrete wearing course pavement surface. The results of this study have also found that the relationship model between asphalt content and the skid resistance value of the asphalt concrete wearing course pavement surface is y= -2.8543x +87.965, R2= 0.8279. The relationship model between density and the surface skid resistance value of the asphalt concrete wearing course pavement, y = -85.006x + 2621.46, R2 = 0.935. This means that the higher the asphalt content and the density of the asphalt concrete wearing course pavement, the lower the surface skid resistance.